Protection of public interests by narrowing private interests: where is the limit? - Клепікова, Ольга Вікторівна; Клепікова, О. В.; Клепикова, Ольга Викторовна; Klepikova, Olha V.; Klepikova, Olga; Качурінер, Вікторія Львівна; Качурінер, В. Л.; Качуринер, Виктория Львовна; Kachuriner, Viktoriia L.; Макода, Володимир Євгенович; Макода, В. Є.; Макода, Владимир Евгеньевич; et al. (My University, 2021)
The coronavirus pandemic (COVID-19) has posed many challenges to the international community. In a pandemic, governments make complex decisions every day (respond quickly to emerging difficulties), implement effective quarantine measures that affect the public and private interests of the people. Such decisions are also made by such supranational entities as the European Union. With this in mind, it is essential to analyze the interaction and balance of private and public interests in EU law in the context of the Covid-19 pandemic. The work aims to analyze the balance between private and public interests in EU law in the context of the Covid19 pandemic. Research methods are such methods as dialectical, historical, idealization, analysis, synthesis, abstraction, system, formalization, comparison, and modeling. As a result of the study, the authors concluded that the search for a balance between public and private interests is in all areas and mostly applies to human rights and, in a pandemic, these powers are enshrined in major international treaties and national regulations, with reservations about their possible limitation under exceptional circumstances. At the same time, ensuring the balance of private and public interests is possible only if the rule of law is fulfilled in the implementation of restrictive measures, proportionality, and public necessity.

Пандемія, спричинена коронавірусною інфекцією (COVID-19) поставила багато викликів перед міжнародною спільнотою. В умовах пандемії уряди країн приймають складні рішення кожного дня (швидко реагувати на нововиявлені труднощі), впроваджувати ефективні карантинні заходи, які впливають на публічні та приватні інтереси людей. Відповідні рішення приймаються і таким наддержавним утворенням, як Європейський Союз. З огляду на це важливо проаналізувати взаємодію та баланс приватних та публічних інтересів в праві ЄС в умовах пандемії Covid-19. Метою роботи є аналіз дотримання балансу між приватними та публічними інтересами в праві ЄС в умовах пандемії Covid-19. Методами дослідження є такі методи як діалектичний, історичний, ідеалізації, аналіз, синтез, абстрагування, системний, формалізації, порівняння та метод моделювання. В результаті проведеного дослідження, автори дійшли висновку, що пошук балансу між публічними та приватними інтересами є у всіх сферах та значною мірою стосується прав людини та, в умовах пандемії, ці правомочності закріплені в головних міжнародно-правових договорах та національних нормативно-правових актах, із застереженнями щодо можливого їх обмеження за виключних умов. При цьому, забезпечення балансу приватних і публічних інтересів можливе тільки за умов дотримання законності при впровадженні обмежувальних заходів, пропорційності та суспільній необхідності.
Protection of public interests by narrowing private interests: where is the limit? / O. Klepikova, V. Kachuriner, V. Makoda, I. Kryvosheyina, V. Popeliuk // Amazonia Investiga. - Vol. 10. - Issue 38. - Universidad de la Amazonia, 2021. - Р. 148-157.
Keywords: public interest; private interest; EU law; quarantine restrictions; enforcement; Covid19 pandemic; публічний інтерес; приватний інтерес; право ЄС; карантинні обмеження; забезпечення прав; пандемія Covid-19; Research Subject Categories::LAW/JURISPRUDENCE